2013
DOI: 10.1186/1742-4933-10-15
|View full text |Cite
|
Sign up to set email alerts
|

Stress responses, vitagenes and hormesis as critical determinants in aging and longevity: Mitochondria as a “chi”

Abstract: Understanding mechanisms of aging and determinants of life span will help to reduce age-related morbidity and facilitate healthy aging. Average lifespan has increased over the last centuries, as a consequence of medical and environmental factors, but maximal life span remains unchanged. Extension of maximal life span is currently possible in animal models with measures such as genetic manipulations and caloric restriction (CR). CR appears to prolong life by reducing reactive oxygen species (ROS)-mediated oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(76 citation statements)
references
References 67 publications
3
73
0
Order By: Relevance
“…Vitagenes encode for heat shock proteins Hsp32 and Hsp70, the thioredoxin and the sirtuin protein systems (Calabrese et al, 2008). Dietary antioxidants have recently been demonstrated to be protective through the activation of hormetic pathways, including vitagenes (Cornelius et al, 2013), such as both melatonin and resveratrol that promote SIRT1 protein expression (Fig. 4) (Allard et al, 2009;Tajes et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Vitagenes encode for heat shock proteins Hsp32 and Hsp70, the thioredoxin and the sirtuin protein systems (Calabrese et al, 2008). Dietary antioxidants have recently been demonstrated to be protective through the activation of hormetic pathways, including vitagenes (Cornelius et al, 2013), such as both melatonin and resveratrol that promote SIRT1 protein expression (Fig. 4) (Allard et al, 2009;Tajes et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…However, recent findings have revealed that ROS formation is likely not the main cause of aging (Hekimi et al, 2011) and while chronic high levels of ROS can produce cellular damage, contributing to the aged phenotype, low levels are implicated in cellular stress responses and survival mechanisms, which are highly regulated processes controlled by a complex network of intracellular signaling pathways (López-Otín et al, 2013). By sensing the intracellular nutrient and energy status, the functional state of mitochondria, and the concentration of ROS produced in mitochondria, the longevity network regulates lifespan across species by coordinating information flow along multiply diverse signaling pathways, including vitagenes which are genes involved in preserving cellular homeostasis during stressful conditions (Cornelius et al, 2013). Vitagenes encode for heat shock proteins Hsp32 and Hsp70, the thioredoxin and the sirtuin protein systems (Calabrese et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, many nonthermal stimuli also denature proteins, such as oxidative stress, mitochondrial collapse, hypoxia, irradiation, endoplasmic reticulum stress, and physical trauma, and these stimuli often also induce heat shock protein synthesis (Aridon et al 2011;Lanneau et al 2010). Heat shock proteins are so essential for life and well conserved across species that the genes encoding some of these proteins have been termed "vitagenes" by Vittorio Calabrese and his colleagues (Calabrese et al , 2012Cornelius et al 2013). Despite the integrated network of chaperones and co-chaperones, proteins cannot always be folded back into their native shapes, especially when they are severely damaged.…”
mentioning
confidence: 99%
“…Hormesis is defined as favorable reactions to low-level stress and has been observed in the toxicological literature for many decades (4)(5)(6)(7)47). Hormesis elicits U-shaped or biphasic responses to stress and is mediated, at least in part, by the co-ordinated network of vitagenes (8)(9)(10)20). Preconditioning increases the expression of the vitagenes thioredoxin, sirtuin-1, Hsp32, and Hsp70 (1,2,16,59).…”
Section: Ape1 Preserves Neuronal Structure and Functionmentioning
confidence: 99%
“…Mild cellular stress is known to engage the vitagene network of pro-survival proteins such as heat shock proteins 70 (Hsp70), Hsp32 (also known as heme oxygenase 1), thioredoxin, and sirtuin-1 (8,10,20). In order to examine whether PI also increased vitagenes, we probed for Hsp32, Hsp70, thioredoxin, and sirtuin-1 ( Supplementary Fig.…”
Section: Ape1 Induction Mediates the Neuroprotective Effect Of Pi Andmentioning
confidence: 99%